LWD PUSJATAN SEBAGAI ALAT ALTERNATIF DALAM MENGEVALUASI PERKERASAN LENTUR (IRE’S LWD AS ALTERNATIVE TOOL FOR FLEXIBLE PAVEMENT TEST) - Siegfried Syafier (Jurnal Jalan-Jembatan, 2018)
The structural strength testing is required to evaluate an existing pavement. The common equipment used for this sort of testing is Falling Weight Deflectometer (FWD. Especially in Indonesia, the availability of FWDs is very limited except in Java island. The alternate equipment for this purpose is to use the IRE’s LWD. This type of LWD is slightly different to that of standard ones, where the IRE’s LWD does not use load cell. The load parameter depends on the height of drops which is calibrated on the laboratory. Another thing is that the IRE’s LWD has higher stress level because its load is higher than the standard ones. This study is to look for the possibility of the use of IRE’s LWD as the alternate equipment for FWD on the flexible pavement as well as to find the correlation between these equipment in terms of surface modulus. The main parameters considered in this study are the surface modulus on the load point (E0) and surface modulus in the 900 mm offset (E1). The site for this study is at IRE campus which is classified as medium to low volume flexible roads. It is found that there is a strong correlation between surface modulus obtained from FWD test and that of IRE’s LWD. This is indicated by the plotting between each modulus around the equality line as well as by their coefficient correlation. This findings assure that it is possible to use the IRE’s LWD as the alternative for FWD for evaluation flexible roads which are classified as the medium to low traffic flexible roads. Keywords: IRE’s LWD, FWD, surface modulus, flexible pavement evaluation, medium to low traffic roads.